2019
DOI: 10.7717/peerj.6820
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of thallium(I) on rutile nano-titanium dioxide and environmental implications

Abstract: Rutile nano-titanium dioxide (RNTD) characterized by loose particles with diameter in 20–50 nm has a very large surface area for adsorption of Tl, a typical trace metal that has severe toxicity. The increasing application of RNTD and widespread discharge of Tl-bearing effluents from various industrial activities would increase the risk of their co-exposure in aquatic environments. The adsorption behavior of Tl(I) (a prevalent form of Tl in nature) on RNTD was studied as a function of solution pH, temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Considerable experimental and theoretical efforts have been directed toward understanding the cytotoxic effects and interaction mechanisms of metal-based NPs; however, the potential risks associated with metal-based NPs do not allow their routine use in clinical medicine. Metal-based NPs exhibit size, surface, and quantum properties that may lead to abnormal features in adsorption, [5] chemical reaction, [6] dispersion or agglomeration, [7,8] and tissue penetration. [9] The cytotoxicity of metal-based NPs depends on their composition, size, shape, surface charge, solubility, coating material, and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable experimental and theoretical efforts have been directed toward understanding the cytotoxic effects and interaction mechanisms of metal-based NPs; however, the potential risks associated with metal-based NPs do not allow their routine use in clinical medicine. Metal-based NPs exhibit size, surface, and quantum properties that may lead to abnormal features in adsorption, [5] chemical reaction, [6] dispersion or agglomeration, [7,8] and tissue penetration. [9] The cytotoxicity of metal-based NPs depends on their composition, size, shape, surface charge, solubility, coating material, and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to determine that cinnamon essential oil is not causing alterations or modifications in the crystalline structure of CaCO 3 . Similarly, in Figure 2B, the diffractogram of TiO 2 reveals the crystallographic planes (110), ( 101), ( 200), ( 111), ( 210), ( 211), ( 220), ( 002), (310), (301), and (112) [24,25]. This is consistent with the results of Joni et al [26], who worked with TiO 2 nanoparticles in the rutile phase and reported positions at 2θ of 27.42 • , 36.08 • , 41.25 • , 54.33 • , and 63.44 • , corresponding to the crystallographic planes mentioned in this article.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 63%
“…The comparison of the Q m value for Tl(I) removal by various adsorbents are listed in Table 3 . This table included inorganic adsorbents (such as multiwalled carbon nanotubes [ 22 ], polyacrylamide-aluminosilicate composites [ 22 ] and nano-titanium dioxide [ 58 ]). It was seen that NOCNF extracted from sorghum stalks possessed the highest Q m value (almost twice of those for titanate nanotube- 709.2 mg/g [ 59 ] and nanosized manganese dioxide-672.7 mg/g [ 19 ]).…”
Section: Resultsmentioning
confidence: 99%